THE EFFECT OF RELIGIUSITY, UNDERSTANDING OF TAXATION AND LOVE OF MONEY ON PERCEPTION OF TAX EVASION WITH TAX EDUCATION AS A MODERATING VARIABLE - Linawati Linawati (Jurnal Ekonomi, 2022)
This study aims to examine the effect of religiosity, understanding of taxation, and love of money on perceptions of tax evasion and examine tax education to moderate the relationship between religiosity, understanding of taxation, and love of money on perceptions of tax evasion. The method used in this research is a descriptive method with a quantitative approach. The population in this study were Diploma students of the Pamulang University accounting study program. The stages of the research method start with collecting data through questionnaires. The sampling technique was determined based on purposive sampling; then, the data was processed using multiple linear regression analysis. The results showed that the first hypothesis, namely, religiosity positively affects the perception of tax evasion, was rejected. The second hypothesis is that tax understanding does not affect tax evasion because the results prove tax understanding. The third hypothesis of love of money does not affect tax evasion is rejected. The fourth hypothesis is rejected because tax education does not moderate the relationship between religiosity on perceptions of tax evasion. The fifth hypothesis is accepted because tax education can moderate the relationship between tax understanding and perceptions of tax evasion. The sixth hypothesis is accepted because tax education does not moderate the relationship between the love of money and perceptions of tax evasion.